Systematic Simulation of Disordered Cylindrical Nanoporous Materials - Ubaldo Gil-Cruz; Salomón Cordero-Sánchez; Juan Villegas-Cortez; Rafael Villalobos-García (Adsorption Science & Technology)
This paper describes a simple method, based on the Dual Site–Bond Model, for constructing disordered cylindrical porous substrata. Heterogeneity is accounted for by allowing the presence of variable cross-sectional areas along the length of the pore tubes forming the solid. The degree of heterogeneity is easily controlled with overlapping between the pore-size distributions of pore cavities and pore necks. Some simulated materials with different textural properties are presented. An analysis of the texture of the generated structures, together with their nitrogen adsorption characteristics, has been carried out and is discussed.